Romanticismo sociale nei ripostigli di un mondo illuminato. Elogio delle infermiere e degli infermieri nei reparti psichiatrici di acuzie - Kruse, Gunther (Il sogno della farfalla, 2012)
After having offered a brief summary of the history of German social psychiatry of the last 40 years, above all out of the hospital context, the author describes how the community and public opinion currently tend to have mental reservations of and offer accusations against hospital psychiatry, without ever appreciating the work they do. The author then outlines the problems of difficult patients (not to be confused with those patients whose treatment is difficult) and goes on to describe how the nursing staff of closed psychiatric wards is constantly involved in the improbable task of squaring the circle, treading warily amidst bureaucratic excesses, psychiatric theories and personal self-denial.